Un nuovo Duvalius del "gruppo Cerrutii" (Sensu Magrini, 1997) del Lazio meridionale (Italia) (Coleoptera: Carabidae: Trechinae) - Magrini, Paolo (Acta entomologica slovenica (Ljubljana), 2003)
Duvalius laurentii sp. n. from Central Italy Chiavica n°1 senza fondo Cave, N° 603 La/Fr, 500 m a., Amaseno (Frosinone); Ausoni Mountains; Latium is described. The new species differs from the species of "Cerrutii Group" already described from Latium and Campania (Duvalius cerrutii Sbordoni & Di Domenico, 1967; Duvalius oscus Franzini & Franzini, 1984; Duvalius carchinii Vigna, Magrini & Vanni, 1993; Duvalius vannii Magrini & Sclano, 1998; Duvaliusbastianinii Magrini, 1998; Duvalius bertagnii Magrini, 1998) in its habitus and male copulatory apparatus.
Keywords: entomologija; hrošči; Italija; Italy